Kajian Efektivitas Rute Layanan BRT Koridor Rajabasa-Panjang - Rahmani, Siti; Putra, Sasana; Karami, Muhammad; Sulistyorini, Rahayu (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2019)
One of the public transportations in Bandar Lampung is the BRT Rajabasa-Panjang corridor. However, due to the lack of interest of the community to use public vehicles specifically for BRT, only one of the seven corridors operated.The purpose of this study was to determine and analyze the effectiveness of BRT Transport Service Routes in the Rajabasa-Panjang corridor with the effect of effectiveness measured by service frequency, load factor, head way, travel speed, and standardized departure time as service performance indicators.The results of this study are the average speed of BRT Rajabasa-Panjang route, which is 26.25 km/hr, and from Panjang-Rajabasa route is 27.87 km/hr. For the average value of Load Factor on the Rajabasa-Panjang route is 38.23 % and on the Panjang-Rajabasa route is 38.80%. From the results of the data obtained, the Time Headway value is obtained at 16.5 minutes and the value of service frequency is equal to 4 vehicles/hour. The average cycle time on BRT is Monday and Friday, which is 2 hours 49 minutes and Saturday is only 2 hours 28 minutes. The number of bus fleets needed is 10 units for one cycle. Keywords: load factor, time headway, service frequency, speed, fleet requirements, bus effectiveness.